Peran Kelompok Tani dalam Penerapan Teknologi Pertanian - Sri Nuryanti; Dewa Ketut Sadra Swastika (Forum penelitian Agro Ekonomi, 2011)
EnglishThis paper describes roles of farmers’ groups in agricultural technology application. A farmers’ group is defined as a group of farmers informally consolidate themselves based on their common goals in farming activities. Initial spirit of establishing a farmers’ group is to strengthen farmers’ bargaining position, especially in terms of collective purchasing of farm inputs and selling their agricultural products efficiently. Indonesia has a long experience in formation of farmers’ groups since Mass Intensification (BIMAS) and Special Intensification (INSUS) were launched in 1970s-1980s. Currently, most of farmers groups in Indonesia are not formed by farmers themselves, but they are mostly formed as a response to the government program that requires farmers to become members of a farmers’ group. Most of government support for farmers, such as distribution of subsidized fertilizer, agricultural extension, subsidized farm credits and other programs are distributed to farmers’ group or farmers’ groups association. Introduction and promotion of a new technology is also delivered through farmers’ groups. Thus, the roles of a farmers’ group are not only as the means of distributing government assistance and extension services, but also as the agent for new technology adoption.  IndonesianMakalah ini merupakan tinjauan (review) dari berbagai literatur dan hasil penelitian terdahulu, ditujukan untuk mendeskripsikan peran kelompok tani dalam penerapan teknologi pertanian. Kelompok tani didefinisikan sebagai sekelompok petani yang secara informal mengkonsolidasi diri berdasarkan kepentingan bersama dalam berusahatani. Semangat awal pembentukan kelompok tani adalah untuk memperkuat posisi tawar, terutama dalam pengadaan sarana produksi dan pemasaran hasil secara kolektif. Indonesia mempunyai pengalaman panjang pembentukan kelompok tani, sejak diluncurkannya program BIMAS, INSUS dan Supra Insus di era 1970-an dan 1980-an. Saat ini kebanyakan kelompok tani di Indonesia tidak lagi dibentuk atas inisiatif petani dalam memperkuat diri, melainkan kebanyakan merupakan respon dari program-program pemerintah yang mengharuskan petani berkelompok. Umumnya program-program bantuan pemerintah seperti: penyaluran pupuk bersudsidi, penyuluhan teknologi pertanian, kredit usahatani bersubsidi, dan program-program lain disalurkan melalui kelompok tani atau gabungan kelompok tani (Gapoktan). Petani yang ingin mendapat teknologi baru dan berbagai program bantuan pemerintah harus menjadi anggota kelompok atau anggota Gapoktan. Dengan demikian, peran kelompok tani tidak hanya sebagai media untuk menyalurkan bantuan-bantuan pemerintah, tetapi juga sebagai agen penerapan teknologi baru.